Effects of dietary extruded linseed and Lactobacillus acidophilus on growth performance, carcass traits, plasma lipoprotein response, and caecal bacterial populations in broiler chicks - A. Gheorghe; N. A. Lefter; L. Idriceanu; M. Ropotă; M. Hăbeanu (Italian Journal of Animal Science, 2020)
The study aimed to assess the effects of dietary extruded linseed (ELS) and Lactobacillus acidophilus (LA) on performance, carcass traits, immune organ weights, plasma lipoprotein response, and caecal bacteria populations in broiler chickens. A total of 648 one-day-old chicks were divided into six groups in a 3 × 2 factorial arrangement consisting of three ELS levels (0, 6 and 12%) without or with probiotic L. acidophilus (0 and 20 g ton−1 feed). Each group had six replicates (18 birds/pen). Results showed no significant effects of ELS level nor LA supplementation on growth performance (body weight gain, feed intake, and feed conversion) of broilers during the overall period (1–42 days). The production efficiency factor increases (p = .045) with the LA addition. There were no effects of ELS level nor probiotic addition on carcase traits and immune organ weights, except for decreases in abdominal fat percentage (p = .027, respectively p = .035). The dietary ELS level significantly correlated with a decrease in the plasma total cholesterol (TC; p = .003), triglycerides, and very-low-density lipoprotein concentrations (p = .020), while the LA addition significantly correlated with a decrease (p = .015) in the plasma TC. The LA addition lowers the caecal pH (p = .007), Staphylococcus spp. and E. coli counts (p < .0001), and increase the caecal Lactobacillus spp. and lactobacilli: E. coli ratio (p < .0001). In conclusion, the use of ELS up to 12% supplemented with L. acidophilus in broiler chicks diet had a positive effect on health status, decreasing the abdominal fat deposition, plasma lipids and the caecal pathogen bacteria E. coli.Highlights Extruded linseed up to 12% in broiler chicks’ diets had no significant effects on growth performance, carcass traits or immune organs size and improve the abdominal fat deposition and plasma lipids response due to the decreased dietary n − 6: n − 3 PUFA ratio. Extruded linseed up to 12% supplemented with L. acidophilus in broiler chicks diet had a positive effect on health status improving production efficiency factor and decreasing abdominal fat deposition, the plasma lipids and the caeca pathogen bacteria E. coli.